2020
DOI: 10.1002/14651858.cd007568.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Telephone interventions for symptom management in adults with cancer

Abstract: BackgroundPeople with cancer experience a variety of symptoms as a result of their disease and the therapies involved in its management. Inadequate symptom management has implications for patient outcomes including functioning, psychological well-being, and quality of life (QoL). Attempts to reduce the incidence and severity of cancer symptoms have involved the development and testing of psycho-educational interventions to enhance patients' symptom self-management. With the trend for care to be provided nearer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 99 publications
2
76
0
2
Order By: Relevance
“…It is also important for nurses to explore other approaches to the management of pain that are not so traditional, but they fit more to the needs of people in the contemporary society. 27,28 As far as efficient and effective use of medication is concerned, the same research showed that nurses have insufficient knowledge regarding opioid analgesics, risks of addiction and tolerance to opioids and systematic pain assessment. 29 These shortcomings can be tackled with more education on pain management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important for nurses to explore other approaches to the management of pain that are not so traditional, but they fit more to the needs of people in the contemporary society. 27,28 As far as efficient and effective use of medication is concerned, the same research showed that nurses have insufficient knowledge regarding opioid analgesics, risks of addiction and tolerance to opioids and systematic pain assessment. 29 These shortcomings can be tackled with more education on pain management.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important for nurses to explore other approaches to the management of pain that are not so traditional, but they fit more to the needs of people in the contemporary society. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…Integrative medicine typically includes personalized "high-touch" services, such as acupuncture and massage, as well as group programs in yoga, music, and other modalities, making a transition to remotely delivered care challenging. Even before the onset of the COVID-19 pandemic, the use of technology (e.g., mobile health [8] or telephone [9]) to support cancer treatment-related symptom management (e.g., depression, anxiety, fatigue) [9] has been on the rise. However, with the exception of exercise-related studies [8], most previously tested mobile health or telephone-based oncology symptom management approaches have not focused on integrative oncology interventions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even before the onset of the COVID-19 pandemic, the use of technology (e.g., mobile health [8] or telephone [9]) to support cancer treatment-related symptom management (e.g., depression, anxiety, fatigue) [9] has been on the rise. However, with the exception of exercise-related studies [8], most previously tested mobile health or telephone-based oncology symptom management approaches have not focused on integrative oncology interventions [9]. To this point, little has been described about how integrative oncology services offered by National Cancer Institute-Designated Cancer Centers have been transformed in response to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The gap in comprehensive care is calling for continuous multidisciplinary care service for optimal patient management which has been reported beneficial to prognosis [8]. In addition, systemic FU management at the government level in China has not been established as in European and American countries [9,10]. Therefore, the major challenge in clinical practice in China is that clinicians have no evidence-based protocol regarding follow up meeting patients' needs and for subgroup patients, for example, for patients with poor accessibility to health facilitates or with comorbidities, or with financial stress.…”
Section: Introductionmentioning
confidence: 99%